4D dynamic imaging of the eye using ultrahigh speed SS-OCT - Liu, Jonathan J.; Grulkowski, Ireneusz; Potsaid, Benjamin; Jayaraman, Vijaysekhar; Cable, Alex E.; Kraus, Martin; Hornegger, Joachim; Duker, Jay S.; Fujimoto, James G. (Proc. SPIE 8567, 2013)

Automated lamina cribrosa microstructural segmentation in optical coherence tomography scans of healthy and glaucomatous eyes - Nadler, Zach; Wang, Bo; Wollstein, Gadi; Nevins, Jessica; Ishikawa, Hiroshi; Kagemann, Larry; Sigal, Ian; Ferguson, Daniel; Hammer, Daniel; Grulkowski, Ireneusz; Liu, Jonathan J.; Kraus, Martin; et al. (Biomedical Optics Express, 2013)
We demonstrate an automated segmentation method for in-vivo 3D optical coherence tomography (OCT) imaging of the lamina cribrosa (LC). Manual segmentations of coronal slices of the LC were used as a gold standard in parameter selection and evaluation of the automated technique. The method was validated using two prototype OCT devices; each had a subject cohort including both healthy and glaucomatous eyes. Automated segmentation of in-vivo 3D LC OCT microstructure performed comparably to manual segmentation and is useful for investigative research and in clinical quantification of the LC. © 2013 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2013.tech.IMMD.IMMD5.automa_57

Automated three-dimensional choroidal vessel segmentation of 3D 1060 nm OCT retinal data - Kajic, Vedran; Esmaeelpour, Marieh; Glittenberg, Carl; Kraus, Martin; Hornegger, Joachim; Othara, Richu; Binder, Susanne; Fujimoto, James G.; Drexler, Wolfgang (Biomedical Optics Express, 2013)

Automatic No-Reference Quality Assessment for Retinal Fundus Images Using Vessel Segmentation - Köhler, Thomas; Budai, Attila; Kraus, Martin; Odstrcilik, Jan; Michelson, Georg; Hornegger, Joachim (2013 26th IEEE International Symposium on Computer-Based Medical Systems (CBMS), 2013)

Choroid, Haller's, and Sattler's Layer Thickness in Intermediate Age-Related Macular Degeneration With and Without Fellow Neovascular Eyes - Esmaeelpour, Marieh; Ansari-Shahrezaei, Siamak; Glittenberg, Carl; Nemetz, Susanne; Kraus, Martin; Hornegger, Joachim; Fujimoto, James G.; Drexler, Wolfgang; Binder, Susanne (Investigative Ophthalmology & Visual Science, 2014)
CONCLUSIONS. The 3D 1060-nm OCT choroidal imaging visualized significant changes in choroidal, Sattler's, and Haller's layer thickness in relation to the progression of AMD. This may be important for understanding the choroidopathy in the pathophysiology of AMD.
Keywords: age-related macular degeneration; optical coherence tomography; choroidal thickness maps; retina; choroid; retina

Deep OCT angiography image generation for motion artifact suppression - Hoßbach, Julian; Husvogt, Lennart; Kraus, Martin; Fujimoto, James G.; Maier, Andreas (Informatik aktuell, 2020)
Eye movements, blinking and other motion during the acquisition of optical coherence tomography (OCT) can lead to artifacts, when processed to OCT angiography (OCTA) images. Affected scans emerge as high intensity (white) or missing (black) regions, resulting in lost information. The aim of this research is to fill these gaps using a deep generative model for OCT to OCTA image translation relying on a single intact OCT scan. Therefore, a U-Net is trained to extract the angiographic information from OCT patches. At inference, a detection algorithm finds outlier OCTA scans based on their surroundings, which are then replaced by the trained network. We show that generative models can augment the missing scans. The augmented volumes could then be used for 3-D segmentation or increase the diagnostic value.
CRIS-Team Scopus Importer:2020-04-21

Depth-encoded all-fiber swept source polarization sensitive OCT - Wang, Zhao; Lee, Hsiang-Chieh; Ahsen, Osman Oguz; Lee, Byungkun; Choi, Woojhon; Potsaid, Benjamin; Liu, Jonathan; Jayaraman, Vijaysekhar; Cable, Alex; Kraus, Martin; Liang, Kaicheng; Hornegger, Joachim; et al. (Biomedical Optics Express, 2014)
Polarization sensitive optical coherence tomography (PS-OCT) is a functional extension of conventional OCT and can assess depth-resolved tissue birefringence in addition to intensity. Most existing PS-OCT systems are relatively complex and their clinical translation remains difficult. We present a simple and robust all-fiber PS-OCT system based on swept source technology and polarization depth-encoding. Polarization multiplexing was achieved using a polarization maintaining fiber. Polarization sensitive signals were detected using fiber based polarization beam splitters and polarization controllers were used to remove the polarization ambiguity. A simplified post-processing algorithm was proposed for speckle noise reduction relaxing the demand for phase stability. We demonstrated systems design for both ophthalmic and catheter-based PS-OCT. For ophthalmic imaging, we used an optical clock frequency doubling method to extend the imaging range of a commercially available short cavity light source to improve polarization depth-encoding. For catheter based imaging, we demonstrated 200 kHz PS-OCT imaging using a MEMS-tunable vertical cavity surface emitting laser (VCSEL) and a high speed micromotor imaging catheter. The system was demonstrated in human retina, finger and lip imaging, as well as ex vivo swine esophagus and cardiovascular imaging. The all-fiber PS-OCT is easier to implement and maintain compared to previous PS-OCT systems and can be more easily translated to clinical applications due to its robust design. (C) 2014 Optical Society of America

Efficient and high accuracy 3-D OCT angiography motion correction in pathology - Ploner, Stefan; Kraus, Martin; Moult, Eric M.; Husvogt, Lennart; Schottenhamml, Julia; Yasin Alibhai, A.; Waheed, Nadia K.; Duker, Jay S.; Fujimoto, James G.; Maier, Andreas (Biomedical Optics Express, 2021)
We describe a novel method for non-rigid 3-D motion correction of orthogonally raster-scanned optical coherence tomography angiography volumes. This is the first approach that aligns predominantly axial structural features such as retinal layers as well as transverse angiographic vascular features in a joint optimization. Combined with orthogonal scanning and favorization of kinematically more plausible displacements, subpixel alignment and micrometer-scale distortion correction is achieved in all 3 dimensions. As no specific structures are segmented, the method is by design robust to pathologic changes. Furthermore, the method is designed for highly parallel implementation and short runtime, allowing its integration into clinical workflow even for high density or wide-field scans. We evaluated the algorithm with metrics related to clinically relevant features in an extensive quantitative evaluation based on 204 volumetric scans of 17 subjects, including patients with diverse pathologies and healthy controls. Using this method, we achieve state-of-the-art axial motion correction and show significant advances in both transverse co-alignment and distortion correction, especially in the subgroup with pathology.
CRIS-Team Scopus Importer:2021-01-08

En Face Imaging of the Choroid in Polypoidal Choroidal Vasculopathy Using Swept-Source Optical Coherence Tomography - Alasil, Tarek; Ferrara, Daniela; Adhi, Mehreen; Brewer, Erika; Kraus, Martin; Baumal, Caroline R.; Hornegger, Joachim; Fujimoto, James G.; Witkin, Andre J.; Reichel, Elis; Duker, Jay S.; Waheed, Nadia K. (American Journal of Ophthalmology, 2015)
CONCLUSIONS: En face SS OCT provides an in vivo tool to visualize the pathologic features and the choroidal vasculature in PCV. (C) 2015 by Elsevier Inc. All rights reserved.

Free-Breathing Whole-Heart Coronary MRI: An Image-Based Motion Compensation Integrated Into Compressed-Sensing Reconstruction - Forman, Christoph; Grimm, Robert; Hutter, Jana; Wasza, Jakob; Kraus, Martin; Hornegger, Joachim; Zenge, Michael O. (Proceedings of the 21st Annual Meeting of ISMRM, 2013)
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.IMMD5.freebr_2

GPU Accelerated Time-of-Flight Super-Resolution for Image-Guided Surgery - Wetzl, Jens; Taubmann, Oliver; Haase, Sven; Köhler, Thomas; Kraus, Martin; Hornegger, Joachim (Bildverarbeitung für die Medizin, 2013)

Handheld ultrahigh speed swept source optical coherence tomography instrument using a MEMS scanning mirror - Lu, Chen D.; Kraus, Martin; Potsaid, Benjamin; Liu, Jonathan J.; Choi, WooJhon; Jayaraman, Vijaysekhar; Cable, Alex E.; Hornegger, Joachim; Duker, Jay S.; Fujimoto, James G. (Biomedical Optics Express, 2014)
We developed an ultrahigh speed, handheld swept source optical coherence tomography (SS-OCT) ophthalmic instrument using a 2D MEMS mirror. A vertical cavity surface-emitting laser (VCSEL) operating at 1060 nm center wavelength yielded a 350 kHz axial scan rate and 10 μm axial resolution in tissue. The long coherence length of the VCSEL enabled a 3.08 mm imaging range with minimal sensitivity roll-off in tissue. Two different designs with identical optical components were tested to evaluate handheld OCT ergonomics. An iris camera aided in alignment of the OCT beam through the pupil and a manual fixation light selected the imaging region on the retina. Volumetric and high definition scans were obtained from 5 undilated normal subjects. Volumetric OCT data was acquired by scanning the 2.4 mm diameter 2D MEMS mirror sinusoidally in the fast direction and linearly in the orthogonal slow direction. A second volumetric sinusoidal scan was obtained in the orthogonal direction and the two volumes were processed with a software algorithm to generate a merged motion-corrected volume. Motion-corrected standard 6 × 6 mm2 and wide field 10 × 10 mm2 volumetric OCT data were generated using two volumetric scans, each obtained in 1.4 seconds. High definition 10 mm and 6 mm B-scans were obtained by averaging and registering 25 B-scans obtained over the same position in 0.57 seconds. One of the advantages of volumetric OCT data is the generation of en face OCT images with arbitrary cross sectional B-scans registered to fundus features. This technology should enable screening applications to identify early retinal disease, before irreversible vision impairment or loss occurs. Handheld OCT technology also promises to enable applications in a wide range of settings outside of the traditional ophthalmology or optometry clinics including pediatrics, intraoperative, primary care, developing countries, and military medicine. © 2013 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2014.tech.IMMD.IMMD5.handhe

In vivo imaging of the rodent eye with swept source/Fourier domain OCT - Liu, Jonathan J.; Grulkowski, Ireneusz; Kraus, Martin; Potsaid, Benjamin; Lu, Chen D.; Baumann, Bernhard; Duker, Jay S.; Hornegger, Joachim; Fujimoto, James G. (Biomedical Optics Express, 2013)
Swept source/Fourier domain OCT is demonstrated for in vivo imaging of the rodent eye. Using commercial swept laser technology, we developed a prototype OCT imaging system for small animal ocular imaging operating in the 1050 nm wavelength range at an axial scan rate of 100 kHz with 6 μm axial resolution. The high imaging speed enables volumetric imaging with high axial scan densities, measuring high flow velocities in vessels, and repeated volumetric imaging over time. The 1050 nm wavelength light provides increased penetration into tissue compared to standard commercial OCT systems at 850 nm. The long imaging range enables multiple operating modes for imaging the retina, posterior eye, as well as anterior eye and full eye length. A registration algorithm using orthogonally scanned OCT volumetric data sets which can correct motion on a per A-scan basis is applied to compensate motion and merge motion corrected volumetric data for enhanced OCT image quality. Ultrahigh speed swept source OCT is a promising technique for imaging the rodent eye, proving comprehensive information on the cornea, anterior segment, lens, vitreous, posterior segment, retina and choroid. © 2013 Optical Society of America.

Motion Correction and Signal Enhancement in Optical Coherence Tomography - Kraus, Martin (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2016)
Optical Coherence Tomography (OCT) is a non-invasive optical imaging modality with micron scale resolution and the ability to generate 2D and 3D images of the human retina. OCT has found widespread use in ophthalmology. However, motion artifacts induced by the scanning nature restrict the ability to have reliable quantification of OCT images. Furthermore, OCT suffers from speckle noise and signal quality issues. This work addresses these issues by treating the motion correction problem as a special image registration problem. Two or more 3D-OCT volumes with orthogonal scan patterns are acquired. A custom objective function is used to register the input volumes. As opposed to standard image registration, there is no reference volume as all volumes are assumed to be distorted by motion artifacts. To improve the robustness of the correction algorithm, multi-stage and multi-resolution optimization, illuminationand tilt-correction and custom similarity measures and regularization are employed. After registration, the corrected volumes are merged and a single volume with less noise is constructed by adaptively combining the registered data. A large-scale quantitative evaluation was performed using data acquired from 73 healthy and glaucomatous eyes. Three independent orthogonal volume pairs for each location of both the optic nerve head and the macula region were acquired. The results of two motion correction algorithm profiles were compared with performing no motion correction. The evaluation measured registration performance, reproducibility performance and signal improvement using mutual information, error maps based on the difference of automatic segmentation of retinal features and a no-reference image quality assessment. In all three of these aspects, the proposed algorithm leads to major improvements, in accordance with visual inspection. For example, the mean blood vessel map reproducibility error over all data is reduced to 47% of the uncorrected error. The algorithm has been deployed to multiple clinical sites so far. In addition, the technique has been commercialized. The main application is structural imaging for clinical practice and research. The removal of motion artifacts enables high quality en face visualization of features. The technique has also been applied to hand held OCT imaging and small animal imaging. Furthermore, applications in functional imaging in the form of intensity based angiography and Doppler OCT have been demonstrated. Overall, the motion correction algorithm can improve both the visual appearance and the reliability of quantitative measurements derived from 3D-OCT data substantially. This promises to improve diagnosis and tracking of retinal diseases using OCT data.<br
UnivIS-Import:2018-09-06:Pub.2016.tech.IMMD.IMMD5.motion_1

Motion correction in optical coherence tomography volumes on a per A-scan basis using orthogonal scan patterns - Kraus, Martin; Potsaid, Benjamin; Mayer, Markus Anton; Bock, Rüdiger; Baumann, Bernhard; Liu, Jonathan J.; Hornegger, Joachim; Fujimoto, James G. (Biomedical Optics Express, 2012)
High speed Optical Coherence Tomography (OCT) has made it possible to rapidly capture densely sampled 3D volume data. One key application is the acquisition of high quality in vivo volumetric data sets of the human retina. Since the volume is acquired in a few seconds, eye movement during the scan process leads to distortion, which limits the accuracy of quantitative measurements using 3D OCT data. In this paper, we present a novel software based method to correct motion artifacts in OCT raster scans. Motion compensation is performed retrospectively using image registration algorithms on the OCT data sets themselves. Multiple, successively acquired volume scans with orthogonal fast scan directions are registered retrospectively in order to estimate and correct eye motion. Registration is performed by optimizing a large scale numerical problem as given by a global objective function using one dense displacement field for each input volume and special regularization based on the time structure of the acquisition process. After optimization, each volume is undistorted and a single merged volume is constructed that has superior signal quality compared to the input volumes. Experiments were performed using 3D OCT data from the macula and optic nerve head acquired with a high-speed ultra-high resolution 850 nm spectral OCT as well as wide field data acquired with a 1050 nm swept source OCT instrument. Evaluation of registration performance and result stability as well as visual inspection shows that the algorithm can correct for motion in all three dimensions and on a per A-scan basis. Corrected volumes do not show visible motion artifacts. In addition, merging multiple motion corrected and registered volumes leads to improved signal quality. These results demonstrate that motion correction and merging improves image quality and should also improve morphometric measurement accuracy from volumetric OCT data. © 2012 Optical Society of America.

OCT-OCTA Segmentation: a Novel Framework and an Application to Segment Bruch's Membrane in the Presence of Drusen - Schottenhamml, Julia; Moult, Eric M.; Novais, Eduardo A.; Kraus, Martin; Lee, Byungkun; Choi, Woojhon; Ploner, Stefan; Husvogt, Lennart; Lu, Chen D.; Yiu, Patrick; Rosenfeld, Philip; Duker, Jay S.; et al. (Investigative Ophthalmology & Visual Science, 2017)
Purpose : We present a novel framework for segmenting optical coherence tomography (OCT) and OCT angiography (OCTA) that jointly uses structural and angiographic information. We term this new paradigm “OCT-OCTA segmentation,” and demonstrate its utility by segmenting Bruch’s membrane (BM) in the presence of drusen. Methods : We developed an automatic OCT-OCTA graph-cut algorithm for BM segmentation. Our algorithm’s performance was quantitatively validated by comparing it with manual segmentation in 7 eyes (6 patients; 73.8±5.7 y/o) with drusen. The algorithm was also qualitatively assessed in healthy eyes (n=13), eyes with diabetic retinopathy (n=21), early/intermediate age-related macular degeneration (AMD) (n=14), exudative AMD (n=5), geographic atrophy (GA) (n=6), and polypoidal choroidal vasculopathy (n=7). Results : The absolute pixel-wise error between the manual and automatic segmentations had the following values: mean: 4.5±0.89um; 1st Quartile: 1.9±1.35um; 2nd Quartile: 3.9±1.90um; and 3rd Quartile: 6.3±2.67. This corresponds to a mean absolute error smaller than the optical axial resolution of our OCT system ( 8-9um). In all other tested eyes, qualitative visual inspection showed BM contours that were deemed suitably accurate for use in forming en face OCT(A) projections. The algorithm’s poorest results occurred in GA patients with large areas of atrophy. Conclusions : By leveraging both structural and angiographic information we showed that OCT-OCTA segmentation is likely to be a widely useful framework for segmenting ocular structur
UnivIS-Import:2018-09-11:Pub.2017.tech.IMMD.IMMD5.octoct_8
Keywords: oct; octa; oct angiography; layer segmentation; drusen; diabetic retinopathy

OCT-OCTA Segmentation - Schottenhamml, Julia; Moult, Eric M.; Novais, Eduardo A.; Kraus, Martin; Lee, Byungkun; Choi, WooJhon; Ploner, Stefan; Husvogt, Lennart; Lu, Chen D.; Yiu, Patrick; Rosenfeld, Philip; Duker, Jay S.; et al. (Bildverarbeitung für die Medizin 2018, 2018)
In this work, a novel paradigm for segmenting optical coherence tomography (OCT) and optical coherence tomography angiography (OCTA) is presented [1]. Since it uses OCT and OCTA information jointly it is called “OCT-OCTA segmentation” and its usefulness is demonstrated by segmenting the Bruch’s Membrane (BM) in the presence of drusen. Therefore a fully automatic graph-cut algorithm was developed and evaluated by comparing the automatic segmentation results with manual segmentation in 7 eyes (6 patients; 73.8 ± 5.7 y/o) with nascent geographic atrophy and/or drusen associated geographic atrophy.<br
UnivIS-Import:2018-09-11:Pub.2018.tech.IMMD.IMMD5.octoct

Photoreceptor Lengthening During Dark Adaptation Detected With Ultra-High Resolution Optical Coherence Tomography - Lu, Chen D.; Choi, Woo Jhon; Wang, Zhao; Kraus, Martin; Hornegger, Joachim; Duker, Jay S.; Fujimoto, James G. (Investigative Ophthalmology & Visual Science, 2015)

Piezoelectric-transducer-based miniature catheter for ultrahigh-speed endoscopic optical coherence tomography - Tsai, Tsung Han; Potsaid, Benjamin; Kraus, Martin; Zhou, Chao; Tao, Yuankai K.; Hornegger, Joachim; Fujimoto, James G. (Biomedical Optics Express, 2011)
We developed a piezoelectric-transducer- (PZT) based miniature catheter with an outer diameter of 3.5 mm for ultrahigh-speed endoscopic optical coherence tomography (OCT). A miniaturized PZT bender actuates a fiber and the beam is scanned through a GRIN lens and micro-prism to provide high-speed, side-viewing capability. The probe optics can be pulled back over a long distance to acquire three-dimensional (3D) data sets covering a large area. Imaging is performed with 11 μm axial resolution in air (8 μm in tissue) and 20 μm transverse resolution, at 960 frames per second with a Fourier domain mode-locked laser operating at 480 kHz axial scan rate. Using a high-speed data acquisition system, endoscopic OCT imaging of the rabbit esophagus and colon in vivo and human colon specimens ex vivo is demonstrated. © 2011 Optical Society of America.

Piezoelectric transducer based miniature catheter for ultrahigh speed endoscopic optical coherence tomography - Tsai, Tsung-Han; Potsaid, Benjamin M.; Kraus, Martin; Liu, Jonathan J.; Zhou, Chao; Hornegger, Joachim; Fujimoto, James G. (Optical Coherence Tomography and Coherence Domain Optical Methods in Biomedicine XV, 2011)
We developed a piezoelectric transducer (PZT) based miniature catheter with an outer diameter of 3 mm for ultrahigh speed endoscopic optical coherence tomography (OCT) using Fourier domain modelocked (FDML) laser at a 480 kHz axial scan rate. The miniaturized PZT bender actuates a fiber to provide high scanning speed. The side-viewing probe can be pulled back for a long distance to acquire three-dimensional (3D) dataset covering a large area on the specimen. Operating with a high speed data acquisition (DAQ) system, OCT imaging with 6.5 mm imaging range, 10 μm axial resolution, 20 μm lateral resolution, and frame rate of 480 frames per second (fps) is demonstrated. © 2011 Copyright SPIE - The International Society for Optical Engineering.

Quantitative 3D-OCT motion correction with tilt and illumination correction, robust similarity measure and regularization - Kraus, Martin; Liu, Jonathan J.; Schottenhamml, Julia; Chen, Chieh-Li; Budai, Attila; Branchini, Lauren; Ko, Tony; Ishikawa, Hiroshi; Wollstein, Gadi; Schuman, Joel; Duker, Jay S.; Fujimoto, James G.; et al. (Biomedical Optics Express, 2014)
Variability in illumination, signal quality, tilt and the amount of motion pose challenges for post-processing based 3D-OCT motion correction algorithms. We present an advanced 3D-OCT motion correction algorithm using image registration and orthogonal raster scan patterns aimed at addressing these challenges. An intensity similarity measure using the pseudo Huber norm and a regularization scheme based on a pseudo L-0.5 norm are introduced. A two-stage registration approach was developed. In the first stage, only axial motion and axial tilt are coarsely corrected. This result is then used as the starting point for a second stage full optimization. In preprocessing, a bias field estimation based approach to correct illumination differences in the input volumes is employed. Quantitative evaluation was performed using a large set of data acquired from 73 healthy and glaucomatous eyes using SD-OCT systems. OCT volumes of both the optic nerve head and the macula region acquired with three independent orthogonal volume pairs for each location were used to assess reproducibility. The advanced motion correction algorithm using the techniques presented in this paper was compared to a basic algorithm corresponding to an earlier version and to performing no motion correction. Errors in segmentation-based measures such as layer positions, retinal and nerve fiber thickness, as well as the blood vessel pattern were evaluated. The quantitative results consistently show that reproducibility is improved considerably by using the advanced algorithm, which also significantly outperforms the basic algorithm. The mean of the mean absolute retinal thickness difference over all data was 9.9 um without motion correction, 7.1 um using the basic algorithm and 5.0 um using the advanced algorithm. Similarly, the blood vessel likelihood map error is reduced to 69% of the uncorrected error for the basic and to 47% of the uncorrected error for the advanced algorithm. These results demonstrate that our advanced motion correction algorithm has the potential to improve the reliability of quantitative measurements derived from 3D-OCT data substantially. (C) 2014 Optical Society of America

Retinal blood flow measurement with ultrahigh-speed swept-source / Fourier domain optical coherence tomography - Baumann, Bernhard; Potsaid, Benjamin; Liu, Jonathan J.; Kraus, Martin; Huang, David; Hornegger, Joachim; Duker, Jay S.; Fujimoto, James G. (Ophthalmic Technologies XXI, 2011)
Doppler OCT is a functional extension of OCT that provides information on flow in biological tissues. We present a novel approach for total retinal blood flow assessment using ultrahigh speed Doppler OCT. A swept source / Fourier domain OCT system at 1050 nm was used for 3D imaging of the human retina. The high axial scan rate of 200 kHz allowed measuring the high flow velocities in the central retinal vessels. By analyzing en-face images extracted from 3D Doppler data sets, absolute flow for single vessels as well as total retinal blood flow can be measured using a simple and robust protocol. © 2011 Copyright Society of Photo-Optical Instrumentation Engineers (SPIE).

Split-spectrum amplitude-decorrelation angiography with optical coherence tomography - Jia, Yali; Tan, Ou; Tokayer, Jason; Potsaid, Benjamin; Wang, Yimin; Liu, Jonathan J.; Kraus, Martin; Subhash, Hrebesh; Fujimoto, James G.; Hornegger, Joachim; Huang, David (Optics Express, 2012)
Amplitude decorrelation measurement is sensitive to transverse flow and immune to phase noise in comparison to Doppler and other phase-based approaches. However, the high axial resolution of OCT makes it very sensitive to the pulsatile bulk motion noise in the axial direction. To overcome this limitation, we developed split-spectrum amplitude-decorrelation angiography (SSADA) to improve the signal-to-noise ratio (SNR) of flow detection. The full OCT spectrum was split into several narrower bands. Inter-B-scan decorrelation was computed using the spectral bands separately and then averaged. The SSADA algorithm was tested on in vivo images of the human macula and optic nerve head. It significantly improved both SNR for flow detection and connectivity of microvascular network when compared to other amplitude-decorrelation algorithms. © 2012 Optical Society of America.

Swept source optical coherence microscopy using a 1310 nm VCSEL light source - Ahsen, Osman; Tao, Yuankai Kenny; Potsaid, Benjamin; Sheikine, Yuri; Jiang, James; Grulkowski, Ireneusz; Tsai, Tsung-Han; Jayaraman, Vijaysekhar; Kraus, Martin; Connolly, James L.; Hornegger, Joachim; Cable, Alex E.; et al. (Optics Express, 2013)

Three-Dimensional Enhanced Imaging of Vitreoretinal Interface in Diabetic Retinopathy Using Swept-Source Optical Coherence Tomography - Adhi, Mehreen; Badaro, Emmerson; Liu, Jonathan J.; Kraus, Martin; Baumal, Caroline R.; Witkin, Andre J.; Hornegger, Joachim; Fujimoto, James G.; Duker, Jay S.; Waheed, Nadia K. (American Journal of Ophthalmology, 2016)
CONCLUSION: SSOCT with motion-correction and vitreous windowing provides wide-field 3-dimensional information of vitreoretinal interface in diabetic eyes. This may be useful in assessing progression of retinopathy, planning diabetic vitreous surgery, and predicting treatment outcomes. (C) 2016 by Elsevier Inc. All rights reserved.

Total retinal blood flow measurement with ultrahigh speed swept source/Fourier domain OCT - Baumann, Bernhard; Potsaid, Benjamin; Kraus, Martin; Liu, Jonathan J.; Huang, David; Hornegger, Joachim; Cable, Alex E.; Duker, Jay S.; Fujimoto, James G. (Biomedical Optics Express, 2011)
Doppler OCT provides depth-resolved information on flow in biological tissues. In this article, we demonstrate ultrahigh speed swept source/Fourier domain OCT for visualization and quantitative assessment of retinal blood flow. Using swept laser technology, the system operated in the 1050-nm wavelength range at a high axial scan rate of 200 kHz. The rapid imaging speed not only enables volumetric imaging with high axial scan densities, but also enables measurement of high flow velocities in the central retinal vessels. Deep penetration in the optic nerve and lamina cribrosa was achieved by imaging at 1-μm wavelengths. By analyzing en-face images extracted from 3D Doppler data sets, absolute flow in single vessels as well as total retinal blood flow was measured using a simple and robust protocol that does not require measurement of Doppler angles. The results from measurements in healthy eyes suggest that ultrahigh speed swept source/Fourier domain OCT could be a promising technique for volumetric imaging of retinal vasculature and quantitation of retinal blood flow in a wide range of retinal diseases. © 2011 Optical Society of America.

Ultrahigh speed endoscopic optical coherence tomography using micromotor imaging catheter and VCSEL technology - Tsai, Tsung-Han; Potsaid, Benjamin; Tao, Yuankai Kenny; Jayaraman, Vijaysekhar; Jiang, James; Heim, Peter J. S.; Kraus, Martin; Zhou, Chao; Hornegger, Joachim; Mashimo, Hiroshi; Cable, Alex E.; Fujimoto, James G. (Biomedical Optics Express, 2013)
We developed a micromotor based miniature catheter with an outer diameter of 3.2 mm for ultrahigh speed endoscopic swept source optical coherence tomography (OCT) using a vertical cavity surfaceemitting laser (VCSEL) at a 1 MHz axial scan rate. The micromotor can rotate a micro-prism at several hundred frames per second with less than 5 V drive voltage to provide fast and stable scanning, which is not sensitive to the bending of the catheter. The side-viewing probe can be pulled back to acquire a three-dimensional (3D) data set covering a large area on the specimen. The VCSEL provides a high axial scan rate to support dense sampling under high frame rate operation. Using a high speed data acquisition system, in vivo 3D-OCT imaging in the rabbit GI tract and ex vivo imaging of a human colon specimen with 8 μm axial resolution, 8 μm lateral resolution and 1.2 mm depth range in tissue at a frame rate of 400 fps was demonstrated. © 2013 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2013.tech.IMMD.IMMD5.ultrah_8

Ultrahigh speed endoscopic optical coherence tomography using micro-motor imaging catheter and VCSEL technology - Tsai, Tsung-Han; Tao, Yuankai Kenny; Potsaid, Benjamin; Jayaraman, Vijaysekhar; Kraus, Martin; Heim, Peter J. S.; Hornegger, Joachim; Mashimo, Hiroshi; Cable, Alex E.; Fujimoto, James G. (Optical Coherence Tomography and Coherence Domain Optical Methods in Biomedicine XVII, 2013)
We developed a micro-motor based miniature catheter with an outer diameter of 3mm for ultrahigh speed endoscopic vbvvvoptical coherence tomography (OCT) using vertical cavity surface-emitting laser (VCSEL) at a 1MHz axial scan rate. The micro-motor can rotate a micro-prism at 1,200-72,000rpm (corresponding to 20- 1,200fps) with less than 5V driving voltage to provide fast and stable scanning, which is not sensitive to the bending of the catheter. The side-viewing probe can be pulled back for a long distance to acquire three-dimensional (3D) dataset covering a large area on the specimen. VCSEL provides high a-line rate to support dense sampling under high frame rate operation. With the use of a C++ based high speed data acquisition (DAQ) system, in vivo three-dimensional OCT imaging in rabbit GI tract with 1.6mm depth range, 11μm axial resolution, 8μm lateral resolution, and frame rate of 400fps is demonstrated. © 2013 Copyright SPIE.